PENGARUH GERHANA MATAHARI 09 MARET 2016 TERHADAP KANDUNGAN TOTAL ELEKTRON IONOSFER - Vita, Aprilia Nur; Sunardi, Bambang; Sulastri, Sulastri; Sakya, Andi Eka (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Total electron content in the ionosphere is affected by several factors, local time, solar activity, geomagnetic disturbance, geographical latitude and longitude. This research aims to observe level variation of total electron content during solar eclipse over Indonesia on 09 March 2016. We analyzed GPS data from two GPS stations in different locations with different suns obscuration magnitude, which are Bitung Station (BTNG) and Yogyakarta station (JOG2). The magnitude of solar eclipse in Bitung Area was 0.97, while the solar eclipse magnitude in Yogyakarta reached 0.849. In addition, the data are obtained a day before, during, and a day after the solar eclipse, then compared to investigate the anomaly. Data from the previous day and a day after the solar eclipse assumed as normal data. From the result, it shows that more significant TEC anomaly recorded in Bitung if comparing with TEC variation in Yogyakarta. Keywords: Total Electron Content, ionosphere, solar eclipses, GPS, Yogyakarta, Bitung